Erythropoietic protoporphyria - Kansky, Aleksej (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2004)
Erythropoietic protoporphyria (EPP) is caused by the accumulation of protoporphyrin in the red blood cells and is characterized by extreme photosensitivity. Large scale clinical investigations of EPP patients became possible in the mid 60s, when relatively simple spectrophotometric laboratory tests for porhyrins in biological material were introduced. Patients with EPP have been studied in most European countries and in the USA. It was consideredto be an autosomal dominant hereditary disorder, but research in thelast few years has shown that two alleles are involved: one mutated allele and a second wild-type allele that is only partially active. In symptomatic patients the level of enzyme activity is 1030% of the normal, and latent carriers characteristically display around 50%. Common absorbent sunscreens offer very little protection compared to reflectant preparations, and particularly those that contain very small particles of TiO2 and ZnO.
Keywords: dermatologija; Diagnosis; eritropoeza; Genetics; kožne bolezni; Mutacija; mutacije; Mutation; Porfirija eritropoetična; Porphyria, Erythropoietic; Protoporfirini; Protoporphyrins; Therapy; zdravljenje